Hypoplastic left heart with complete transposition of the great arteries. - Lang, D (1985)
A male newborn infant with hypoplastic left heart and transposition of the great arteries died on the second day of life. The haemodynamic consequences of this malformation are considerably different from those of ordinary hypoplastic left heart syndrome because of pulmonary rather than aortic atresia. In the absence of cross sectional echocardiographic equipment, cardiac catheterisation with angiography is necessary to delineate the anatomical picture. These two conditions have not apparently been reported before in association.